(untitled) (International Journal of Physiotherapy, 2014)
Background: Peri-menopause is the stage immediately preceding menopause & lasts on average 4yrs. The hormonal changes in peri-menopausal women alter the cardiovascular status & increase the incidence of obesity. The purpose of this study is to improve physical activity of women to combat this risk in peri-menopausal women by using structured exercise protocol. Methods: A total of thirty peri-menopausal women who met inclusive criteria participated in this study with age between 35-45yrs. They were randomly divided into 2 groups-experimental group (group 1, n=15) and control group (group 2, n=15), a 12-week exercise protocol were given under supervision for experimental group. The experimental group underwent the protocol of warm up for 10min following 25min exercise protocol and 10min of cool down period. The same exercise protocols were followed by control group without supervision. Results: According to data analysis, a significant difference was found between pre and post values of BMI, WHR, Physical activity level and vo2 peak in both experimental and control groups(p<0.05), but comparatively more significant changes were found in experimental rather than control group(p<0.05). Conclusion: There was a significant change in physical factors like BMI, WHR and physical activity level and functional factors like vo2 peak. Hence, it is concluded that 12weeks exercise protocol is effective in peri-menopausal women.